Pengaruh Kemitraan terhadap Kondisi Sosial Ekonomi Petani dan Lembaga Mitra (Suatu Kasus di Asosiasi Aspakusa Makmur) - Wulandari, Maria Winanda; Nadapdap, Hendrik Johannes (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2020)
A partnership is a business strategy that is cultivated in a cooperative relationship between two or more parties with each other's principles of need, raising, and mutual benefit. The goal is to know the impact of partnerships formed between farmers partners with Aspakusa Makmur Association, know the influence of partnership factors namely communication, cooperation, trust, commitment, and conflict on the social partnership conditions of farmers partners and Aspakusa Makmur Association and know the influence of acceptance, experience, land tenure, and relationship value to the economic partnership condition of farmers partner and Aspakusa Makmur Association. The research methods used are surveys. Sampling using a simple random sampling technique of 53 respondents. The implementation of research started in January - February 2020. Data analysis uses descriptive analysis and multiple linear regression. The results showed that the partnership pattern formed as a general trade partnership pattern. Variable cooperation (X2) and commitment (X4) have a significant influence on the social partnership conditions (Y1), while the communication (X1), trust (X3), and conflict (X5) do not have a significant influence on the social partnership conditions (Y1). Variable acceptance (X6) and relationship value (X9) have a significant influence on the economic partnership conditions (Y2), while the experience (X7) and land tenure (X8) do not have a significant influence on the economic partnership conditions (Y2). The need to expand the market for increased sales and profits, it will increase the number of partner farmer supply and minimize the possibility of stacking and rejection of crop yields.